Re-Entry Evaluation of Chinese Blood Donors with Unconfirmed Hepatitis B Screening Results - Deng, Xuelian; Zang, Liang; Candotti, Daniel (Viruses, 2022)
The hepatitis B virus (HBV) remains a high priority for Chinese blood banks due to the high prevalence of infection. HBV blood safety has been significantly improved by the implementation of highly sensitive and specific serological and molecular HBV screening assays. The multiplication of viral markers tested and the ever-increasing analytical sensitivity of the tests can make the interpretation of the results difficult. False-positive or indeterminate results may lead to permanent donor deferrals and conflicts between donors and blood banks. To avoid blood shortages, blood services aim to limit unnecessary donor losses by developing procedures for the re-entry of donors temporarily deferred due to an unconfirmed HBV reactivity. The development of such procedures based on donor follow-up and HBV confirmation remains limited. A review of the scarce data available revealed considerable heterogeneity in testing methods and re-entry algorithms, limited validation studies, and a lack of accurate assessment of the residual infectious risk potentially associated with donor re-entry. In conclusion, systematic and widely validated confirmatory testing and prolonged follow-up are essential for safe re-entry of temporary deferred donors. Standardization of HBV testing methods and the establishment of dedicated expert laboratories are needed because of the complexity of HBV infection in blood donors.